Велика Россия. Прирастать ее богатства будут Сибирью (Тюменский государственный университет, 2006)
История Ямало-Ненецкого автономного округа интересна и самобытна. В древние времена Нижняя Обь входила в «волости подданные» Великого Новгорода, а после его падения перешла под протекторат Великих Московских князей. Этапным для Севера был поход Ермака в Западную Сибирь, после которого был отстроен Обдорск (Салехард), что открыло русским купцам и царскому правительству путь в тундру. С этого времени территория современного Ямала стала составной частью Российского государства. The history of the Yamalo-Nenets Autonomous Okrug is interesting and original. In ancient times, Nizhny Ob was part of the «volosts of the subjects» of Veliky Novgorod, and after its fall it came under the protectorate of the Grand Dukes of Moscow. Ermak's campaign in Western Siberia was a milestone for the North, after which Obdorsk (Salekhard) was rebuilt, which opened the way for Russian merchants and the tsarist government to the tundra. Since that time, the territory of modern Yamal has become an integral part of the Russian state.